Simultaneous Metal Object Detection and Coil Alignment for Wireless EV Chargers Using Planar Coil Array - Zhang, Wenbiao; Mo, Qingqing; Yan, Pengxu; Liu, Yaoyao (IEEE transactions on instrumentation and measurement, 2021)
For the commercialization of wireless electric vehicle (EV) chargers, the metal object detection and coil alignment are needed for the safe and efficient operation of chargers. This article proposes a dual-purpose method for the simultaneous metal object detection and coil alignment using a planar coil array before the start of wireless EV charging. Magnetic induction tomography (MIT) is adopted to reconstruct the images of metal objects and the location of the objects is calculated using the image processing algorithms. The receiving coil in the EV is visualized using the induced voltage map from the coil array and the coil position is computed using characteristic points of the map. First, the structure of the coil array is optimized using the finite element model (FEM) and 4× 4 coil elements are used. Then the FEM simulation is conducted for the feasibility study of the proposed method. Finally, an experimental setup of the wireless charging is designed for further verification. For the metal object detection, eight experimental cases prove that the proposed method is able to detect and visualize metal objects with different numbers and different shapes. In addition, the maximum location error for all metal objects is 6.27 mm. For the coil alignment, the location error of the receiving coil is less than 2 cm. The proposed method can help to remove metal objects and assist the driver during the parking, which meets the requirement for wireless EV charging.